STUDY ON BRAND EQUITY TOWARDS PURCHASING INTENTION OF HALAL PRODUCTS AMONG YOUNG ADULTS - Muhammad Syukri Mohd Ashmir Wong; Norazlina Mamat; Shofiyyah Moidin; Farrah Payyadah Borhan; Nur Hafizah Harun; Noor Alyani Binti Mohamed Pesri (Journal of Islamic, Social, Economics and Development, 2023)
The branding aspect is very important for every business’s succession whether it consists of products or services. This is because a brand is like a name that will give a life for every product to keep striving and maintaining in the market with the other competitors especially from a different brand but marketing of the same products. The purchasing intention of people on every product influenced mostly by the brand of the products. Moreover, under the branding aspect there are varieties of brand equity that could become the influential factors in purchasing intention for people. The respondents involved in this survey was young adults as they are mostly become the target consumers by the marketers for their product market. This research aims to investigate three of the brand equity including brand personality, brand preference and brand loyalty to see how those brand aspects influenced the purchasing intention of halal products among the young adults. This research used a set of semi-structured questionnaires and have been actively involved with 225 respondents from Academy of Contemporary Islamic Studies UiTM Shah Alam. All data that has been collected were analyzed by using a tool of analysis namely SPSS version 21. From the result, it seems that all variable in this research which are brand personality, brand preference and brand loyalty have the positive relationship towards the purchase intention of halal products.